Organized Crime in the 21st Century Motivations, Opportunities, and Constraints - Nelen, Hans.; Siegel, Dina. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This edited volume brings together the most recent research about various aspects of organized crime and the responses that have developed worldwide as a result to contain serious criminal acts. This book focuses particularly on the way criminal networking and illegal markets have developed during the first two decades of the 21st century. It examines how these developments have influenced the motivations and opportunities to commit organized crime. The volume not only focuses on illegal activities in illegal markets, such as drug and human trafficking, but also addresses organized crime and deviance in various legitimate industries. The contributions were presented at seminars of the Centre for Information and Research on Organized Crime (CIROC), and will be of particular interest to organized crime scholars and researchers, as well as advanced students of criminology across the world.
Chapter 1. Setting the scene -- Part. 1 Markets and networks -- Chapter 2. The Development and Surges of Organized Crime: An Application of Enterprise Theory -- Chapter 3. The organisation of crime in the transnational adoption market -- Chapter 4. Drug crime and the port of Rotterdam: About the phenomenon and its approach -- Chapter 5. Drug-related organized crime in the Meuse Rhine EU-region and the role of national borders -- Chapter 6. 'Clan Crime' in Germany: Migration Politics, Socio-economic Conditions and Intergenerational Transmissions of Criminal Behavior -- Chapter 7. Arab Organized Crime in Israel -- Chapter 8. The h200d office: the local embeddedness of the Dutch Crips gang -- Chapter 9. Contract Killings by Organised Crime Groups: The Spread of Deadly Violence -- Part 2. Responses -- Chapter 10. The criminalization of the trade in wildlife -- Chapter 11. Policing the Environment: The Prosecution of Wildlife and Environmental Crimes -- Chapter 12. Why The Hague Convention Isn't Enough: addressing enabling environments for criminality in intercountry adoption -- Chapter 13. Tackling criminal family networks in the Netherlands: observations & approaches -- Chapter 14. Are Dark Number Estimates of Crime Feasible and Useful?.
Keywords: Transnational crime; Crime -- Sociological aspects; Organized crime; Psychology; Transnational Crime; Crime and Society; Organized Crime; Behavioral Sciences and Psychology